ANALISIS TERHADAP KASUS HUKUM PERDATA DALAM SENGKETA LAHAN PERTANAHAN - Widiawati, Ani; Firmanto, Fakhry; Miswar, Miswar (Jurnal Pahlawan, 2024)
Civil Law is a provision that applies to regulate the rights and obligations of a person in society. One form of part of civil law is land disputes. The results of this study are seen from the purpose of the study, namely how the legal analysis of several types of land dispute cases including customary land disputes, inheritance land disputes, land disputes between residents, and land disputes between communities and other related agencies. And in resolving land disputes, these are resolved through the courts (litigation) and outside the courts (non-litigation) or better known as alternative dispute resolution. All of these cases and their resolution will be carried out in accordance with applicable laws and regulations. One of them is based on Law No. 5 of 1960 concerning Basic Agrarian Principles (UUPA) which must be carried out openly and in cash. The clear and cash nature is the nature of land sale and purchase according to customary law which is recognized based on article 5 of the UUPA which reads: the agrarian law applicable to the earth, water and space is customary law, as long as it does not conflict with national and state interests, which are based on national unity, with Indonesian socialism and with the regulations contained in this law and with other laws and regulations, all things by paying attention to elements that are based on religious law. Land disputes often reap conflicts in society, because of that the conflicts that occur are resolved according to the legal regulations in force in Indonesia. Keywords : Analysis of civil law, land dispute cases, land.